Experiential Learning and Pedagogical Skill Development among Pre-Service Teachers in Teaching Practice Programs: An Academic Analysis - Nirmala, Nirna; Nuraini, Hery; Widiarti, Aniek; Forsia, Lastry (LPPM Universitas Negeri Jakarta, 2025)
This study examines the role of Field Experience Practice (PPL) as an experiential learning platform in developing pre-service teachers’ pedagogical skills. Using a qualitative descriptive approach, the research analyzes how students from Economic Education and English Language Education programs apply lesson planning, classroom management, and assessment skills during PPL at SMA Mutiara Insan Nusantara. Data were gathered through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. Findings indicate that PPL effectively enhances pedagogical competence by linking theory with real teaching experiences. Students successfully implemented student-centered strategies such as Problem-Based Learning (PBL), Think-Pair-Share (TPS), and role play, improving student engagement and critical thinking. Despite challenges in classroom adaptation, reflective practice proved essential for professional growth. The study concludes that PPL fosters pedagogical excellence and recommends strengthening mentorship, technology integration, and reflective learning to support 21st-century teacher education.